German business software giant to regain regional lead. - Hadfield, Will (MEED: Middle East Economic Digest, 2008)
The article looks at the prediction of possibility that business software company SAP will be regaining is leading position in the Middle East. Oracle moved ahead of SAP, gaining about 32 percent of the market in 2006. SAP is now expected to make up the gap with Oracle in 2008, according to IDC, after changing its distribution arrangements in the region. Vinay Nair, analyst at IDC, says that Oracle probably excelled in 2007, but in 2008, it will be even again.